Determinan Loyalitas Konsumen - Sintia Ayu Syafriani (Institut Agama Islam Negeri Padangsidimpuan, 2019)
Hospitality is an inseparable part of the tourism sector that can improve the economy of the country in general and in particular regions. Demand for hotels that are comfortable in North Sumatra based on statistical data released by North Sumatra BPS continues to increase. Thus, it raises the level of hotel competition to increase consumer loyalty. Madani Hotel Medan's management is no exception to always improve in order to be able to compete with other hotels. That is why researchers are interested in knowing consumer loyalty at Madani Hotel Medan. The sample is 100 consumers. The results showed that service quality, price and customer satisfaction have a partial and simultaneous influence on consumer loyalty